Phenotype Detection of Genetic Enzymes B- Lactamase Isolation of Patients with Urinary Tract Infections Bacteria Escherichia Coli - Ali Hassoun Hammadi (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: the main cause of multidrug resistant bacteria is the production of ?-lactamase enzymes. Theobjective of this study was to determine the prevalence of genotype of Escherichia coli spp. isolated fromnosocomial urinary tract infections (UTI). Methods: In a cross-sectional study from May 2019 to January2020, mid-stream urine specimens were collected from 210 patients presented with acute urinary tractinfections whom attending Al- Shahid Ghazi and Al-Hariri Hospital in Medical City/ Baghdad. Sampleswere cultured for E. coli isolation. Antibiotic sensitivity test and the prevalence of resistance enzymeproducing gen were investigated. Results: A total of 210 E. coli were isolated, multidrug resistance strainof E coli (92.85%) was reported by this study. PCR technique indicated that 88.57% of ESBL-producingisolates possessing blaTEM, 30% blaCTX-M genes and 20.48% blaSHV genes between isolates and E. colistill the less resistant to carbapenem due to low expression of KPC gen. Conclusion: ESBLs and KPC werethe higher prevalent genotype of multidrug resistant E. coli in urine sample.